National income matters affect on personal income tax revenue compliance in Malaysia? An eviews approach - Ong, Yih Tat; Nga, Lay Hui Janice; Lee, Chen Hiung Andy (Faculty of Business, Economics and Accountancy, 2021)
Gross Domestic Income (GDP) and Gross National Income (GNI) often in used to measure the economy to ensure higher income and tax collection in a country. Meanwhile, the purpose of audit enforcement by Inland Revenue Board of Malaysia (IRBM) always aims to higher tax compliance and followed by increase the tax collection. The study therefore attempts to examine the significant determinants of personal income tax compliance in Malaysia. A quantitative approach was taken with secondary data obtained from Inland Revenue Board Malaysia (IRBM) and the Malaysian Economic Planning Unit, from the years 2002 to 2017 were used to generate the results. An EViews approach was test for the proposed hypothesis. The study supported the effect GDP and GNI on Individual Income Tax Collection with a significant of 5%. The results a 1% increase in GDP results in a 603.04% increase in personal income tax collection, ceteris paribus with positive association. Surprisingly, a 1% increase in GNI results in a -395.95% in personal income tax collection, ceteris paribus with negative association. The paper validated and expanded on prior research on the relationship between GDP and GNI to personal income tax revenue compliance. Additionally, it has significant implications for the Ministry of Finance and other relevant local authorities in enhancing the personal income tax collection strategy. Theoretical and practical implication are highlighted.